DETERMINANTS OF WILLINGNESS TO PAY FOR BIOSECURITY MEASURES AMONG POULTRY FARMERS: A MITIGATION RESPONSE TO BIRD FLU INCIDENCE IN NIGERIA - B. Okpukpara (Journal of Animal and Plant Sciences, 2016)
In February 2006, the first confirmed case of bird flu in Nigeria was reported at Sambawa Farms. Recently in 2015, there was another outbreak of bird flu in Lagos and other states in Nigeria. The majority of the subsequent outbreaks occurred in Commercial and Semi-Commercial poultry with few outbreaks in the village/rural poultry farms. Nigerian government took measures to curtail the outbreaks and to prevent re-occurrence through culling the infected birds and training on the use of biosecurity measures. Many of these measures were possible through donor funds, which is mostly one-off assistance. However, after withdrawal of this assistance, the sustainability of use of biosecurity measures depends on the farmers’ ability and willingness to pay. Many researches have been conducted on poultry diseases in Nigeria, little or none of these researches has been able to examine the farmers’ willingness to pay for biosecurity measures. This is very critical and important in sustainability of bird flu preventive measures when the assistance of government, donors and NGOs are withdrawn. Thus in orders to achieve the broad objectives of this study, many questions were asked: what factors encourage or discourage farmers’ willingness to pay for biosecurity measures? What determines willingness to pay for biosecurity measures across scales of poultry operations? The major findings of the study include that willingness to pay for biosecurity measures varied across the flock size and adoption of biosecurity measures was positively associated with scale of poultry operation and education of the farmer. The major recommendation of this study is that policy makers should consider socioeconomic characteristics of the farmer and the flock size in setting price for payment of biosecurity measures. Thus, study provided a useful insight on how to make the poor participate in their country efforts to control the disease.
Keywords: Willingness to pay; Poultry; Biosecurity measures